2008
DOI: 10.1111/j.1526-4637.2007.00335.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Mu-Opioid Antagonists in the Treatment of Opioid-Induced Bowel Dysfunction: Systematic Review and Meta-analysis of Randomized Controlled Trials

Abstract: Insufficient evidence exists for the safety or efficacy of naloxone or nalbuphine in the treatment of OBD. Long-term efficacy and safety of any of the opioid antagonists is unknown, as is the incidence or nature of rare adverse events. Alvimopan and methylnaltrexone both show promise in treating OBD, but further data will be required to fully assess their place in therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
2
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 35 publications
1
27
2
4
Order By: Relevance
“…Safety and efficacy of the drug have been evaluated in multiple randomized controlled trials (RCT), and it has been found to reduce POI by a range of 7.5 to 22 hours. 12,[14][15][16][17][18] The most common adverse side effects were constipation, dyspepsia, flatulence, anemia, hypokalemia, back pain, and urinary retention.…”
Section: Treatmentmentioning
confidence: 99%
“…Safety and efficacy of the drug have been evaluated in multiple randomized controlled trials (RCT), and it has been found to reduce POI by a range of 7.5 to 22 hours. 12,[14][15][16][17][18] The most common adverse side effects were constipation, dyspepsia, flatulence, anemia, hypokalemia, back pain, and urinary retention.…”
Section: Treatmentmentioning
confidence: 99%
“…As they do not cross the bloodbrain-barrier, they are used for diminishing peripheral side effects of opioids such as constipation, nausea and vomiting, while maintaining analgesic efficacy. A meta-analysis supports the efficacy of methylnaltrexone and alvimopan, while there is insufficient evidence for other antagonists such as naloxone and nalbuphine [46]. Methylnaltrexone bromide, a peripheral mu opioid receptor antagonist, has already been approved for the treatment of opiate-induced constipation in patients with advanced illness.…”
Section: Opioid Antagonistsmentioning
confidence: 97%
“…Ils ne franchissent pas la barrière hématoencéphalique et ont vocation à réduire les effets indésirables des opiacés comme la constipation, les nausées et les vomissements, sans interférer sur leur action antalgique. Une méta-analyse récente a retenu l'efficacité de la méthylnaltrexone et de l'alvimopan mais pas des autres antagonistes que sont la naloxone et la nalbuphine [19]. Le bromure de méthylnaltre-xone (Relistor ® ) a déjà une AMM en France dans le traitement de la constipation liée aux opiacés chez les patients ayant une pathologie avancée relevant des soins palliatifs lorsque la réponse aux laxatifs habituels est insuffisante.…”
Section: Antagonistes Opioïdesunclassified